Using traditional rituals in hospitality to gain value: A study on the impact of Feng Shui. (June 2018) - Ogilvie, Madeleine; Ng, Danny; Xiang, Erwei; Ryan, Maria M.; Yong, Jaime
Abstract: Superstition and the rituals used to support such beliefs remain an important part of Chinese business society. With the advance of globalisation and the normalisation of many business practices this study explores the importance these rituals continue to play in the contemporary hospitality setting. The paper examines the prominence of Feng Shui in business today in a qualitative study using Chinese restaurants to explore associated business behaviours and perceived value of use. Findings from 20 phenomenological interviews from across four different Asian communities are discussed highlighting the core elements of this ritualistic practice. Results indicate that these practices continue to be used widely, have significant impact in managing the servicescape, and, influence the decisions and behaviours of proprietors. Feng Shui ritual plays an important role in the creation of value for business proprietors who practice it and a conceptual framework on how these rituals provide value is proposed.